Швидкий алгоритм ремаршрутизації в мережах із технологією MPLS в умовах дії відмов - Hatamleh, Hazem (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
The problem of nonlinearity identification in experimental data is considered with application of appropriate statistical tests. An analysis of known statistical nonlinearity test is presented that is based on Fisher relation, and a new simplified test is proposed that can be used in conditions of incomplete experimental or statistical data. The empirical statistical nonlinearity criterion is computed on the basis of existence of a link between the values of respective cumulative sum and sample based standard deviation. It was empirically established that there exists a close link between the proposed and existing tests in the sense of similarity of final testing results. To find the critical values of statistics that are necessary for statistical decision making with the use of the simplified test appropriate computational experiments have been fulfilled. It has also been established that the test proposed can be used successfully in conditions of complete and incomplete experimental data. The practical application of the test proposed to actual data proved the similarity of results obtained with various approaches.